THE IMPACT OF PRENATAL EXPOSURE TO ENDOCRINE DISRUPTING CHEMICALS ON LANGUAGE DEVELOPMENT TRAJECTORIES - (:unkn) unknown (My University, 2024)
Environmental contaminants that can impact and disrupt the endocrine system, known as endocrine disrupting chemicals (EDCs), are of growing concern, found in water, air, and common household goods. The disruption to the endocrine system can have severe impacts on the development of the fetus, particularly with regards to neurodevelopment. Understanding and elucidating the effects of prenatal exposure to EDCs on neurodevelopment will help us develop policies and interventions that minimize exposure and risk. In this research, we examined the effects of prenatal exposure to EDCs and their impact on language development trajectories using two enhanced risk autism cohorts. Chapter 1 introduces the concepts of neurodevelopment, endocrine disruption, the EDCs we intend to examine, and the statistical methods we intend to use in this research. Chapter 2 examines the effect that autism diagnostic status has on language development trajectories, with the hypothesis that those with a diagnosis of autism or that present with sub-clinical symptoms are at greater risk of abnormal development. Our results indicated that children with a diagnosis of autism, or who present with sub-clinical symptoms are at a greater risk of falling into an abnormal language trajectory. Chapter 3 examines the effects of prenatal exposure to phthalates on language development trajectories, with the hypothesis that increased exposure results in greater risk of abnormal development. Our results indicated that low molecular weight phthalates tended to increase risk, while high molecular weight phthalate metabolites tended to decrease risk, though only a few reached statistical significance. Chapter 4 examines the effects of prenatal exposure to air toxics on language development trajectories, with the hypothesis that increased exposure will lead to greater risk of abnormal development. Our results indicated that nearly all air toxics did not have significant effect on risk of abnormal language development, with only acetaldehyde showing a decreased risk. Chapter 5 discusses the previous chapters and the implications of our findings. This research highlights the need for further research in a larger and more representative population, and that the effects of EDCs need to be more thoroughly explored to better elucidate their effects on neurodevelopment.